2014
DOI: 10.1039/c4dt00956h
|View full text |Cite
|
Sign up to set email alerts
|

Observation of magnetoelectric coupling and local piezoresponse in modified (Na0.5Bi0.5)TiO3–BaTiO3–CoFe2O4 lead-free composites

Abstract: Lead-free particulate multiferroic composites of [0.94(Na0.5Bi0.5)TiO3-0.06 BaTiO3]:(Co0.6Zn0.4)(Fe1.7Mn0.3)O4 were synthesized and magnetoelectric (ME) properties were studied. X-ray diffraction and microstructural studies indicated the formation of a two-phase composite system without any impurities. The shift of Raman modes corresponding to ferroelectric and ferrite phases was assigned to the induced strain amid the formation of a two-phase system, in relation to the fraction of each phase in the samples. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(17 citation statements)
references
References 42 publications
3
14
0
Order By: Relevance
“…Figure 3(a) clearly shows tetragonal BTO nanoparticles with particle size ~ 49 nm which is accordance with the XRD results. ) is analogous to the previous reported results [19]. Such type of behaviour in BTO nanoparticles isattributedtopresence of defects as oxygen vacancies on the grains surfaces.…”
Section: 2microscopic Analysissupporting
confidence: 91%
“…Figure 3(a) clearly shows tetragonal BTO nanoparticles with particle size ~ 49 nm which is accordance with the XRD results. ) is analogous to the previous reported results [19]. Such type of behaviour in BTO nanoparticles isattributedtopresence of defects as oxygen vacancies on the grains surfaces.…”
Section: 2microscopic Analysissupporting
confidence: 91%
“…Obviously, the coercive magnetic field of BF–BT:Cr increases from 0.40 T before electrical poling to 0.45 T after electrical poling, which can be attributed to the fact that the electrical poling produces considerable strain in ferroelectric BF–BT:Zn and BF–BT:Cr matrixes. The strain can create hard axis along the poling direction . However, from the almost overlapped M–H loops of BF–BT:Zn before and after electrical poling [Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The strain can create hard axis along the poling direction. [58][59][60] However, from the almost overlapped M-H loops of BF-BT:Zn before and after electrical poling [ Fig. 7(b) and the inset of partly enlarged curve], it is concluded that the BF-BT:Zn has very low magnetoelectric coupling.…”
Section: Resultsmentioning
confidence: 99%
“…The maximum value of α ME is 62.65 and 49.79 mV/cm Oe, respectively, measured for BFTO:Ce and BFTO:La samples. This measurement of α ME indicates an improvement than BTO based multiferroic systems …”
Section: Resultsmentioning
confidence: 64%